Comparative Analysis of Microtendipes Mitogenomes (Diptera: Chironomidae) and Their Phylogenetic Implications - Chao Song; Yiyi Wang; Wenji Wang; Teng Lei; Xin Qi; Luxian Li (Diversity)
Insect mitochondrial genomes are vital to understanding evolutionary relationships and identifying species. This study focused on Microtendipes (Chironomidae), a genus with unresolved phylogenetic positioning and cryptic species challenges. We sequenced and analyzed eight mitogenomes from five Microtendipes species, integrating 23 published Chironominae mitogenomes to reconstruct phylogenies using Maximum Likelihood and Bayesian Inference. The mitogenomes exhibited conserved gene arrangements but variable control region lengths (338–1266 bp) and high AT content (94.14–96.42% in control regions). Our results show that Microtendipes species may be a separate group within the subfamily, while also supporting the monophyly of the Harnischia, Polypedilum, and Chironomus complexes. The monophyly of Microtendipes bimaculus was weakly supported, which may demonstrate the presence of two potential cryptic species. Notably, larval morphology-based species groupings conflicted with the molecular data, suggesting that classifications derived from larval morphological traits may be unreliable. This study advances the evolutionary understanding of Chironomidae and underscores the limitations of single-gene barcodes in species-rich genera.